Profil Fingerprinting Senyawa Dari Ekstrak Kulit Batang Tanaman Tammate (Lannea coromandelica (Hout) Merr.) Menggunakan Analisis FTIR Secara Kemometrik - Muhammad Azwar AR; Muhammad Syahrir; Megawati; Funny Glorita R; Jamaluddin; Hardi (Jurnal Penelitian Pendidikan IPA, 2026)
Lannea coromandelica is a traditional medicinal plant rich in alkaloids, flavonoids, saponins, and tannins with reported antioxidant, antimicrobial, anti-inflammatory, antidiabetic, and antirheumatic activities. Previous studies have primarily emphasized phytochemical screening and pharmacological evaluation, whereas metabolite fingerprint characterization using spectroscopic and chemometric approaches remains limited. This study aimed to characterize the metabolite fingerprint profile of L. coromandelica stem bark extracts using Fourier Transform Infrared (FTIR) spectroscopy and chemometric analysis. Twelve extracts were prepared using maceration, Reflux and sonication with distilled water, ethanol, n-hexane, and ethyl acetate to obtain metabolites with different polarities. FTIR spectroscopy was employed due to its rapid, non-destructive, and reproducible detection of functional groups, while chemometric analysis enhanced extract discrimination and pattern recognition. FTIR spectra revealed O–H, N–H, C–H, C=C, C=O, and C–C functional groups associated with phenolic, aromatic, and alkaloidal compounds related to antioxidant and anti-inflammatory activities. Principal Component Analysis (PCA) showed clear clustering patterns influenced by extraction method and solvent polarity, while Cluster Analysis (CA) demonstrated similarity values of 35.54–99.82% among extracts. These findings confirm that FTIR combined with chemometrics is effective for metabolite fingerprint characterization and quality standardization of L. coromandelica extracts.